Angiosarcoma of the liver in Great Britain in proximity to vinyl chloride sites. Issue 1 (January 1997) - Elliott, P; Kleinschmidt, I
Abstract : OBJECTIVES: To study the incidence of angiosarcoma of the liver in England and Wales 1979-86 and Scotland 1975-87. To investigate whether any non-occupational neighbourhood cases occurred near a vinyl chloride site. METHODS: This is a geographical study of incident cases among the general population of Great Britain. Diagnosis of angiosarcoma of the liver was based mainly on the national cancer registry, the world register of cases among vinyl chloride workers, and the register of cases (including histological review) maintained by the Health and Safety Executive. Proximity (< 10 km) of residence to a vinyl chloride site was based on postcode of address at the time of diagnosis. RESULTS: 55 cases were ascribed to angiosarcoma of the liver in England and Wales with a further six cases in Scotland (annual incidence in Great Britain from all sources of around 1.4 cases per 10 million population). There were two cases with documented exposure to Thorotrast, and 10 cases among vinyl chloride workers. There were no vinyl chloride sites in Scotland. Among the 25 cases in England and Wales with histological diagnosis after review by a panel of pathologists, only 15 were confirmed as angiosarcoma, and one of the two Scottish cases after histological review was also confirmed. Overall, 11 cases ascribed to angiosarcoma were resident within 10 km of a vinyl chloride site; nine were vinyl chloride workers, one further case on histological review was not considered to have been correctly diagnosed as angiosarcoma, and the remaining case, confirmed as angiosarcoma, was employed at a vinyl chloride factory during the late 1950s, although not as a vinyl chloride worker. CONCLUSION: The incidence of angiosarcoma of the liver in Great Britain remains extremely rare. The one confirmed case in a non-vinyl chloride worker within 10 km of a site must nevertheless be presumed to have been exposed to vinyl chloride in the workplace. In the period of study, there were no confirmed non-occupationally exposed cases of angiosarcoma among residents living near a vinyl chloride site in Great Britain.